Functional Impairment of Myeloid Dendritic Cells during Advanced Stage of HIV-1 Infection: Role of Factors Regulating Cytokine Signaling - Sachdeva, Meenakshi; Sharma, Aman; Arora, Sunil K. (PLOS ONE, 2015)
Introduction Severely immunocompromised state during advanced stage of HIV-1 infection has been linked to functionally defective antigen presentation by dendritic cells (DCs). The molecular mechanisms behind DC impairment are still obscure. We investigated changes in DC function and association of key regulators of cytokine signaling during different stages of HIV-1 infection and following antiretroviral therapy (ART). Methods Phenotypic and functional characteristics of circulating myeloid DCs (mDCs) in 56 ART-naive patients (23 in early and 33 in advanced stage of disease), 36 on ART and 24 healthy controls were evaluated. Sixteen patients were studied longitudinally prior-to and 6 months after the start of ART. For functional studies, monocyte-derived DCs (Mo-DCs) were evaluated for endocytosis, allo-stimulation and cytokine secretion. The expression of suppressor of cytokine signaling (SOCS)-1 and other regulators of cytokine signaling was evaluated by real-time RT-PCR. Results The ability to respond to an antigenic stimulation was severely impaired in patients in advanced HIV-1 disease which showed partial recovery in the treated group. Mo-DCs from patients with advanced HIV-disease remained immature with low allo-stimulation and reduced cytokine secretion even after TLR-4 mediated stimulation ex-vivo. The cells had an increased expression of negative regulatory factors like SOCS-1, SOCS-3, SH2-containing phosphatase(SHP)-1 and a reduced expression of positive regulators like Janus kinase(JAK)2 and Nuclear factor kappa-light-chain-enhancer of activated B cells(NF-κB)1. A functional recovery after siRNA mediated silencing of SOCS-1 in these mo-DCs confirms the role of negative regulatory factors in functional impairment of these cells. Conclusions Functionally defective DCs in advanced stage of HIV-1 infection seems to be due to imbalanced state of negative and positive regulatory gene expression. Whether this is a cause or effect of increased viral replication at this stage of disease, needs further investigation. The information may be useful in design of novel therapeutic targets for better management of disease.